Argentine Social Protection in a Context of Demographic Transition - Rofman, Rafael (2016)
Argentina is going through a process of demographic transition that will resultin an older population structure. The demographic transition has direct effectson the quantity and adequacy of social protection transfers, with particularemphasis on those related to pensions. The main objective of this paper is toidentify the potential trends of social protection expenditures in an agingcontext. On the basis of the expenditure profile by age, we apply NationalTransfer Accounts methodology to simulate social protection expenditures until2100. The results suggest that, under various alternative social security coveragescenarios, the demographic transition process would lead to an increase infuture social protection expenditures, reaching 16% of gross domestic product(GDP) by 2050 and exceeding 24% in 2100.